Acute Hemorrhagic Myositis in Inflammatory Myopathy and Review of the Literature. (14th October 2014) - Van Gelder, Howard; Wu, Kim M.; Gharibian, Nayiri; Patel, Dharmi B.; Clements, Philip J.; Heinze, Emil R.; Morris, Robert I.; Wong, Andrew L.
Abstract : We describe two patients with dermatomyositis that presented with interstitial lung disease, positive V and Shawl sign who developed acute spontaneous abdominal/retroperitoneal bleed. Both patients expired despite aggressive treatment and resuscitation. Hemorrhagic myositis in these two patients with inflammatory myopathy is a very rare complication. The association of anti-Ro52 with this potentially very serious complication remains unclear. This potential relationship should be further evaluated in future studies.